“Humor in Da’wah”: Socio-linguistic Analytic of Kyai Ishaq Latif Da’wah from Pesantren Tebuireng Jombang - Asep Abbas Abdullah; Abdul Muhid; Winarto Eka Wahyudi (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2020)
This article aims to describe the anatomy of humor exercised consistently by one of Islamic preachers and teachers from Pesantren Tebuireng, Jombang. This article employs qualitative approach. Kyai Ishaq Latif humor in his sermon analyzed by socio-linguistic perspective. This article found that the Islamic teaching containing theology, family relationship, and social interaction was delivered by him with humor such as anecdotes, acronym., codes, limerick, and satire. Humor has been developed within certain social context. Preacher use humor to be more understood by broader audiences. This article thus suggests that the usage of humor in religious sermons will generate intimacy which enable audience accepted the message without being coerced or offended or intimidated. Humor in religious sermon shows social dialect (sociolect) of the preacher that has integrated with his audiences. The usage of humor is an alternative instrument in delivering holy messages (act sequences) to be accepted effectively by the audiences.Artikel ini bertujuan untuk mengetahui anatomi humor dalam dakwah yang dikembangkan oleh Kiai Ishaq Latif dari Pondok Pesantren Tebuireng Jombang. Melalui pendekatan kualitatif, paper ini dianalisis menggunakan perspektif sosiolinguistik. Hasil penelitian menunjukkan bahwa terdapat beberapa metode humor Kiai Latif antara lain anekdot, akronim, alih kode, pantun dan sindirian. Selain itu, metode humor merupakan “bahasa” yang lahir dari ruang dan konteks sosial tertentu. Bahasa lelucon yang diselipkan dalam dakwah merupakan bentuk guyub tutur yang jamak berlaku di masyarakat awam. Implikasi praksis penelitian ini adalah humor yang ditunjukan oleh seorang pendakwah akan melahirkan keakraban (intimate) yang memungkinkan seseorang menerima ajaran Islam tanpa tekanan, paksaan dan intimidasi. Pada posisi tertentu, humor juga menunjukan dialek sosial (sosialek) seorang pendakwah yang lebih menyatu dengan psikologi masa. Humor diadopsi sebagai instrument untuk membawa amanat suci (act sequences) ajaran agama Islam agar tersampaikan secara efektif bagi masyarakat.